The evolution of offshore renminbi trading: 2016 to 2019 - Yin-Wong Cheung; Louisa Grimm; Frank Westermann (Osnabrück University, Institute of Empirical Economic Research, 2020)
We study the evolution of offshore renminbi trading between 2016 and 2019. The diffusion behaviour of offshore renminbi trading during this period is different from the one between 2013 and 2016. The geographical diffusion process displayed in the 2016-2019 period, in addition to the previously reported convergence to the geographical trading pattern of all currencies, is affected by trade intensity, bilateral swap line arrangements, and has a regional bias. Further, it is possibly affected by disputes with China, and is different from the diffusion behaviours of the offshore US dollar, euro, British pound, and Japanese yen trading.
Keywords: C24; F31; F33; G15; G18; 330; Global Currency; FX Turnover; Geographical Diffusion; Renminbi Internationalization; Trade Intensity